Fenomena Lahn dalam Ritual Ibadah - Taufiqurrochman, Taufiqurrochman (el Harakah: Jurnal Budaya Islam, 2007)
One of the language characteristics is that it is composed of a certain sound system that is distinctive to each other. Alquran that is revealed in Arabic should be articulated appropriately and accurately in order to avoid mistakes, explicitly or implicitly. Lahn is called as solecism in linguistics and catachresis in literature. According to tajwid science (Alquran Phonology), Lahn is defined as. mis pronunciation in reading Alquran. That is why the readers should be able to learn more about tajwid. It is important to avoid making lahn that will change the meaning of the Holly Alquran. This article is aimed at describing lahn phenomenon that appears in religious activities such as adzan, iqamat, tahlil, talbiyah, and praying. Salah satu karakteristik bahasa ialah ia terdiri dari sistem bunyi tertentu yang dapat membedakannya dengan lainnya. Alquran yang tertulis dalam Bahasa Arab harus diartikulasikan dengan tepat dan akurat agar terhindar dari kesalahan baik itu yang tampak maupun yang tersembunyi. Lahn disebut sebagai kesalahan tata bahasa dalam ilmu Linguistik dan catachresis dalam ilmu Sastra. Menurut ilmu Tajwid (Fonologi Alquran), Lahn didefinisikan sebagai kesalahan pengucapan dalam membaca Alquran. Maka dari itu, pembaca harus mempelajari Tajwid lebih jauh lagi. Artikel ini bertujuan untuk mendeskripsikan fenomena Lahn yang tampak dalam aktivitas keagamaan seperti azan, iqamah, tahlil, talbiyah, dan berdoa.